Milestones towards lung cancer screening implementation - Silva, Mario; Milanese, G.; Kauczor, Hans-Ulrich; Revel, M.-P.; Sverzellati, N. (Clinical radiology, 2020)
The European Society of Radiology (ESR) and European Respiratory Society (ERS) published their joint statement paper on lung cancer screening (LCS), on 12 February 2020. This document joins and completes previous recommendations on LCS with specific emphasis on the analysis of issues encountered in the practical implementation of LCS in the community. Major milestones to enable the most efficient and equal dissemination of LCS are recognised as engagement of all stakeholders (e.g. candidate/participant, general practitioners, up to the specialised LCS facility), quality assurance, and primary prevention in the form of provision of counselling for smoking cessation.
Gesehen am 05.01.2021